2010
DOI: 10.1002/etc.408
|View full text |Cite
|
Sign up to set email alerts
|

Resuspension of polychlorinated biphenyl‐contaminated field sediment: release to the water column and determination of site‐specific KDOC

Abstract: Sediments from the New Bedford Harbor (NBH) U.S. Environmental Protection Agency (U.S. EPA) Superfund site (Massachusetts, USA), contaminated with polychlorinated biphenyls (PCBs), were resuspended under different water column redox conditions: untreated, oxidative, and reductive. The partitioning of PCBs to the overlying water column was measured with polyethylene samplers and compared to partitioning without resuspension. Greater concentrations of total aqueous (freely dissolved + dissolved organic carbon (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…36 A similar conclusion was previously reached by Friedman et al, who reported that polychlorinated biphenyls (PCBs) in the New Bedford Harbor estuary sorbed 5−20 times stronger to DOC than predicted. 37 We included results for the DOC correction of apparent dissolved PAH concentrations from liquid−liquid extraction assuming that DOC sorbed PAHs 5 times stronger than predicted by Burkhard,36 resulting in better agreement between HMW PAHs from both methods.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…36 A similar conclusion was previously reached by Friedman et al, who reported that polychlorinated biphenyls (PCBs) in the New Bedford Harbor estuary sorbed 5−20 times stronger to DOC than predicted. 37 We included results for the DOC correction of apparent dissolved PAH concentrations from liquid−liquid extraction assuming that DOC sorbed PAHs 5 times stronger than predicted by Burkhard,36 resulting in better agreement between HMW PAHs from both methods.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The equilibrium status of the target contaminants can be calculated and used to adjust for nonequilibrium conditions by measuring the loss of PRCs following the deployment. There are currently at least three approaches recommended for making the nonequilibrium calculations using the raw PRC concentrations including a first order equation, a diffusion-based model, ,, and a sampling rate-based correction . When using PRCs, it is worth noting that for highly hydrophobic contaminants, the passive sampler may accumulate relatively low concentrations while under nonequilibrium conditions making quantification analytically challenging.…”
Section: Background and Methodsmentioning
confidence: 99%
“…Adams () observed a doubling of C free levels in the Hudson River estuary during spring tide resuspension events; this change was not seen during the neap tides when resuspension was much weaker. Friedman et al () studied the impact of large‐scale resuspension of native sediments on the release of PCBs to the water column using passive samplers. The magnitude of increased concentrations depended on resuspension time and the K ow of the congener ranging from 1 to 8 times those found without resuspension.…”
Section: The Importance Of Determing Equilibrium Concentrationsmentioning
confidence: 99%